Development of the Euplectrus sp. Near Bicolor (Hymenoptera: Eulophidae) on Zonoplusia ochreata (Lepidoptera: Noctuidae) - Namee, J.; Bumroongsook, S. (International Journal of Agricultural Technology, 2018)
The larval ectoparasitoid Euplectrus sp. near bicolor (Eulophidae: Hymenoptera), is a gregarious ectoparasitoid of the pennywort cutworm larvae (Zonoplusia ochreata). Biological investigation of Euplectrus sp. near bicolor was conducted in the laboratory (27-35oC; 60-70%RH). The female adults copulated only once for their life time and deposited eggs singly or in clusters of two to eight eggs on the second or third abdominal segment of their larval hosts, which were mostly in the second or third instars. The parasitoids’ eggs had an incubation period of 1.0–3.3 days (2.61 ± 2.10 days). The larvae stayed in a cluster and did not move until they were ready to pupate. The larval period took 2.1–3.8 days (2.82 ± 0.48 days). Pupation occurred on the underside skin of the dead host in a loosely woven silk cocoon that formed in between the host remains and adjacent leaves. The pupal period was ranged from 5.0–7.9 days (6.42 ± 0.89 days). Mating took place immediately after adult emergence, and the adults lived for 2.9–10.8 days (7.51 ± 2.58 days). The total duration of the life cycle from egg to adult emergence was 13.0–25.8 days.